EFFICACY OF NEWLY FORMULATED OINTMENT CONTAINING 20% ACTIVE ANTIMICROBIAL HONEY IN TREATMENT OF BURN WOUND INFECTIONS - Tasleem, Samiyah; Naqvi, Syed Baqir Shyum; Khan, Saadat Ali; Hashmi, Khursheed (Journal of Ayub Medical College Abbottabad, 2013)
Background: Honey has been familiar to possess antimicrobial potential to clear infection against burn wound infecting bacteria since ancient times. The objective of the study was to evaluate the efficacy of the newly formulated honey ointment during the treatment of burn wound infections. The Experimental (Non comparative) study was conducted at outpatient department of Dermatology, Fauji Foundation Hospital, Rawalpindi from November 2009 to October 2010. Methods: The antimicrobial activity of different Pakistani floral sources (Acacia nilotica species indica, Zizyphus, Helianthus annuus and Carissa opaca) honey samples were investigated by disc diffusion method against freshly isolated burn wounds infecting bacteria. Ointment containing 20% active antimicrobial honey was formulated as a sovereign remedy. A total number of twenty patients with second degree of burn wounds on different parts of the body were studied. A thin layer of honey ointment on gauze was applied to the wounds two to three times a day up to the complete healing. Results: During microbiological study, Pakistani honey samples were discovered to exhibit a very promising antimicrobial activity against all the wound infecting microorganisms tested. Clinical trials demonstrated that the topical application of honey ointment have significant control of infections arising form pathogenic bacteria and up to 100% healing results were observed in all burn wound cases within mean healing time for the duration of 8.15 (3-18) days time period. Conclusion: Newly formulated ointment containing 20% active antimicrobial honey is more effective and low-cost alternative preparation for the treatment of burn wound infections. Keywords: Antimicrobial activity of honey, Honey ointment, Burn wound infections